2018
DOI: 10.1039/c7fo00469a
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic attributes and prevention of LPS-induced pro-inflammatory stress in RAW264.7 macrophages and human intestinal epithelial cell line (Caco-2) by newly isolatedWeissella cibariastrains

Abstract: Probiotic lactic acid bacteria are known to modulate gut associated immune responses. Not many studies have reported on the role of Weissella species in preventing lipopolysaccharide (LPS) induced proinflammatory stress in murine macrophages as well as in human intestinal epithelial cells (Caco-2). Therefore, the present study was taken up to evaluate the probiotic attributes of four newly isolated Weissella strains (two each from fermented dosa batter and a human infant faecal sample); these attributes are ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 32 publications
3
26
0
Order By: Relevance
“…The results of the Caco-2/THP-1 co-culture experiments are provided in Figure 6 . Measurement of IL-6 was performed as known pro-inflammatory signature of LPS-stimulated macrophages, and also of colonic mucosal cells [ 36 , 37 ]. The results showed that preventative treatment with the probiotic with digestive enzymes supplement generated microbial metabolites in the proximal colon reactors that decreased IL-6 concentrations in the co-culture model as compared to the control reactors that were not supplemented but were treated with 5-FU/vancomycin.…”
Section: Resultsmentioning
confidence: 99%
“…The results of the Caco-2/THP-1 co-culture experiments are provided in Figure 6 . Measurement of IL-6 was performed as known pro-inflammatory signature of LPS-stimulated macrophages, and also of colonic mucosal cells [ 36 , 37 ]. The results showed that preventative treatment with the probiotic with digestive enzymes supplement generated microbial metabolites in the proximal colon reactors that decreased IL-6 concentrations in the co-culture model as compared to the control reactors that were not supplemented but were treated with 5-FU/vancomycin.…”
Section: Resultsmentioning
confidence: 99%
“…The dietary supplementation with Weissella koreensis powder improved growth performance in pigs and had a beneficial effect on the immune response during an inflammatory challenge ( Wang et al., 2011 ). A study has revealed that Weissella species played important roles in preventing lipopolysaccharide-induced proinflammatory stress in murine macrophages and in human intestinal epithelial cells ( Singh et al., 2018 ). The Lactococcus genus is considered a potential etiological agent in the mastitis outbreak investigation ( Rodrigues et al., 2016 ), and Lactococcus garvieae is the causative agent of lactococcosis, a hyperacute and hemorrhagic septicemia of fish ( Meyburgh et al., 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…The intestinal barrier is chronically exposed to various antigens including microorganisms and toxin (Gu et al, 2016). LPS, an endotoxin derived from gut gram-negative bacteria, mediates inflammatory reaction and homeostasis disturbance by stimulating the massive production of pro-inflammatory cytokines, such as IL-6, IL-8, and TNF-α (Singh et al, 2018;Wang and Kong, 2018). It has been reported that probiotics could directly interact with the IECs regulating the immune inflammation caused by LPS (Singh et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Considering W. cibaria a relatively recent member of LAB, the occurrence of potential probiotic strains belonging to this species still needs to be explored. Indeed, some specific W. cibaria strains had shown some beneficial effects, demonstrating antioxidant (Ye et al, 2018;Zhu et al, 2018), antimicrobial (Lim et al, 2018), anticancer (Kwak et al, 2018), and immunomodulatory features (Lee et al, 2018;Singh et al, 2018). Singh et al (2018) indicated that W. cibaria 28, a strain isolated from human infant feces, can prevent pro-inflammatory stress in Caco-2 cells challenged with LPS.…”
Section: Introductionmentioning
confidence: 99%